Method and application of preparing micro-nano magnetic composite materials from NdFeB secondary waste

By modifying neodymium iron boron secondary waste by mechanical force chemistry, micro-nanomagnetic composite materials were prepared, which solved the problems of insufficient adsorption performance of neodymium iron boron secondary waste and high cost of arsenic-containing wastewater treatment in mines, and achieved efficient arsenate adsorption and wastewater treatment.

CN118263018BActive Publication Date: 2025-03-11CHINA UNIV OF MINING & TECH +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410342456.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-02-23
Filing Date
2024-03-25
Publication Date
2025-03-11
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

The adsorption performance of neodymium iron boron secondary waste to arsenic is limited and requires modification and treatment to achieve ideal results. At the same time, the treatment of arsenic-containing wastewater in mines has problems of environmental pollution and high economic costs.

Method used

The mechanical force chemistry method is used to modify the secondary waste of neodymium iron boron, and the crystal structure and surface properties of the material are changed by ball milling method to prepare micro-nanomagnetic composite materials for adsorbing arsenate in the arsenic-containing wastewater.

Benefits of technology

The adsorption performance of neodymium-ferrous boron secondary waste to arsenic is improved, the efficient removal of arsenic-containing wastewater in mines is achieved, and the resource utilization of neodymium-ferrous boron secondary waste is achieved simultaneously, reducing environmental pollution and economic costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118263018B_ABST
    Figure CN118263018B_ABST
Patent Text Reader

Abstract

The present invention discloses a method and application of preparing micro-nano magnetic composite materials from NdFeB secondary waste, including: placing NdFeB secondary waste in an oven at 100-110°C, drying for 20-25h and then taking it out; the NdFeB secondary waste is solid waste generated after the NdFeB waste is processed by rare earth recovery; the dried sample of step S1 is subjected to mechanochemical treatment, the mechanochemical treatment is ball milling, the ball milling time is 1-5h, the rotation speed is 100-500rpm, and the ball material mass ratio is 5:1-20:1; the powder after ball milling in step S2 is passed through a 50-mesh sieve, the unscreened powder repeats the ball milling of step S2 until it can pass through a 50-mesh sieve, and the screened powder is placed in a sample bag and sealed for storage. The present invention generates a micro-nano magnetic composite material by subjecting NdFeB secondary waste to high-energy ball milling, which is used to remove As(V) in water, with low cost, green and environmental protection, and high economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a micro-nano magnetic composite material from NdFeB secondary waste and application thereof, belonging to the technical field of solid waste resource utilization and waste well water heavy metal treatment. Background Art

[0002] The mining of mineral resources has caused many environmental problems. For example, mining exposes buried metal sulfide minerals to the surface, which are oxidized by air and microorganisms and washed by rainwater to form acid mine drainage (AMD). Arsenic (As) is one of the main mineralization elements of sulfide minerals. According to statistics, 1732 to 20829 tons of arsenic are mined for every ton of gold mined in my country, and 0.12 to 10.8 tons of arsenic are mined for every ton of other metals except gold. Arsenic exists in AMD in the form of arsenate (As(V)) as sulfide minerals are oxidized and dissolved, and pollutes surrounding rivers and groundwater with the flow of AMD, seeping into farmland, resulting in excessive arsenic content in water and soil. Long-term exposure to arsenic environment will affect the normal function of various organs of the human body and increase the risk of cancer. Arsenic-containing wastewater in mines is not only seriously harmful, widely distributed, but also has a long duration of pollution. Therefore, achieving economic and effective treatment of arsenic-containing wastewater in mines is an inevitable requirement for promoting the sustainable development of the mining industry.

[0003] Among many arsenic removal methods, adsorption is widely used due to its good removal effect, simple operation, and rapid reaction. Solid waste has a wide range of sources and is inexpensive. Using solid waste to prepare adsorption materials to adsorb arsenic can not only achieve its resource recycling, but also achieve the purpose of "waste treatment with waste" in treating arsenic-containing wastewater. NdFeB secondary waste is solid waste generated after NdFeB waste is recycled and treated with rare earths. It contains very few rare earth elements. Its main components are iron oxide and graphite. Its annual output exceeds tens of thousands of tons. It is one of the largest solid waste sources of rare earth enterprises. Long-term storage is prone to land resource occupation and environmental pollution. Therefore, preparing NdFeB secondary waste into adsorption materials for use in the treatment of arsenic-containing wastewater can achieve the comprehensive utilization of NdFeB secondary waste, reduce the harm caused by its long-term stacking to the environment, and improve the economic benefits of enterprises. However, the adsorption performance of NdFeB secondary waste on arsenic is limited, and it needs to be modified to achieve the ideal effect.

[0004] Mechanochemical method, also known as ball milling, is a green and efficient modification method. Its principle is to use mechanical force to grind, compress, shear, and impact the ball milled material, so that the physicochemical properties of the material change, the crystal structure is destroyed, and its surface properties are changed to improve the adsorption performance of the material. Mechanochemical method is widely used in the fields of material surface modification and synthesis, heavy metal separation, solid waste recycling, etc. due to its simple operation, easy control of the reaction process, no need to add other chemical reagents, and more environmentally friendly advantages. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing micro-nano magnetic composite materials from NdFeB secondary waste and its application. The NdFeB secondary waste is modified by a mechanochemical method to be prepared into an adsorption material for use in the treatment of As(V)-containing wastewater, thereby simultaneously realizing the resource recycling of NdFeB secondary waste and the removal of As(V)-containing wastewater, providing a new idea for the comprehensive utilization of NdFeB secondary waste and the preparation of materials by mechanochemical method.

[0006] In order to achieve the above object, the present invention adopts a method for preparing a micro-nano magnetic composite material from NdFeB secondary waste, comprising the following steps:

[0007] S1. Place the NdFeB secondary waste in an oven at 100-110°C and take it out after drying for 20-25 hours; the NdFeB secondary waste is solid waste generated after the NdFeB waste is processed by rare earth recovery;

[0008] S2, subjecting the dried sample of step S1 to a mechanochemical treatment, wherein the mechanochemical treatment is ball milling, the ball milling time is 1 to 5 hours, the rotation speed is 100 to 500 rpm, and the ball-to-material mass ratio is 5:1 to 20:1;

[0009] S3, the powder after ball milling in step S2 is passed through a 50-mesh sieve, and the powder that has not passed the sieve is ball milled again in step S2 until it can pass through a 50-mesh sieve, and the sieved powder is placed in a sample bag and sealed for storage.

[0010] As an improvement, in step S1, the NdFeB secondary waste is placed in an oven at 105° C. and dried for 24 hours.

[0011] As an improvement, the ball milling time in step S2 is 2.5 h, the rotation speed is 400 rpm, and the ball-to-material mass ratio is 10:1.

[0012] As an improvement, the grinding balls used in the ball milling in step S2 are made of cemented carbide.

[0013] As an improvement, the ball milling jar used in the ball milling in step S2 is made of any one of stainless steel, agate, and zirconia.

[0014] In addition, the present invention also provides a micro-nano magnetic composite material prepared by the method.

[0015] Finally, the present invention also provides an application of the micro-nano magnetic composite material in the treatment of arsenic-containing wastewater, comprising the following steps:

[0016] S1. Take 0.03-0.08 g of the prepared micro-nano magnetic composite material, add it to 50 mL of arsenic-containing wastewater with a concentration of 10 mg / L, and adjust the pH of the solution to 2-5;

[0017] S2. Place the pH-adjusted solution in a water bath constant temperature oscillator for oscillation reaction.

[0018] As an improvement, in step S1, the pH of the solution is adjusted to 3.

[0019] As an improvement, the reaction temperature of the water bath constant temperature oscillator in step S2 is 25° C. and the rotation speed is 160 r / min.

[0020] Finally, the present invention also provides an application of the micro-nano magnetic composite material in the treatment of chromium-containing wastewater.

[0021] Compared with the prior art, the present invention adopts the high-energy impact energy in the short-process mechanochemical method to modify the surface properties of the material, regulates the structural changes of the iron oxide mixture in the NdFeB secondary waste, prepares micro-nano magnetic composite materials, achieves high-value resource utilization, and is applied to the treatment of heavy metals such as arsenic in mine wastewater. It has good effect in treating heavy metals, good storage, transportation and stability, and low cost.

[0022] The micro-nano magnetic composite material prepared by the invention has the characteristics of being green, environmentally friendly, recyclable, simple, safe and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD spectrum of the NdFeB secondary waste and the micro-nano magnetic composite material of Example 1 of the present invention;

[0024] Figure 2 SEM images of the NdFeB secondary waste (a) and the micro-nano magnetic composite material (b, c, d) of Example 1 of the present invention;

[0025] Figure 3 Mapping diagrams of NdFeB secondary waste (a, b, c) and micro-nano magnetic composite materials (d, e, f) of Example 1 of the present invention;

[0026] Figure 4 FT-IR images of the NdFeB secondary waste and micro-nano magnetic composite material according to Example 1 of the present invention;

[0027] Figure 5 The micro-nano magnetic composite material of Example 4 of the present invention is affected by pH value and coexisting ions when treating arsenic-containing wastewater;

[0028] Figure 6 The removal mechanism of As (V) by the micro-nano magnetic composite material of the present invention;

[0029] Figure 7 is the removal efficiency of As(V) by the micro-nano magnetic composite material of Example 4 of the present invention after repeated regeneration five times;

[0030] Figure 8 The comparison of the removal effect of the micro-nano magnetic composite material of Example 5 of the present invention on Cr(VI) is shown in FIG1 ;

[0031] Fig. 9 This is the second comparison of the removal effect of the micro-nano magnetic composite material of Example 5 of the present invention on Cr(VI). DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clear, the technical solutions of the present application are described in detail below with the help of accompanying drawings and specific embodiments. It should be understood that the embodiments of the present application and the specific features in the embodiments are detailed descriptions of the technical solutions of the present application, rather than limitations on the technical solutions of the present application. In the absence of conflict, the embodiments of the present application and the technical features in the embodiments can be combined with each other.

[0033] The NdFeB secondary waste in the embodiment comes from a certain company in Ji'an, Jiangxi Province, and its main constituent elements are shown in Table 1.

[0034] Table 1 Composition elements of NdFeB secondary waste

[0035] element Wt / % At / % O 51.9 0.5 C 24.7 0.6 Fe 23.4 0.3 Example 1

[0036] A method for preparing a micro-nano magnetic composite material from NdFeB secondary waste, comprising the following steps:

[0037] S1. Place the NdFeB secondary waste in an oven at 105°C, dry it for 24 hours, then take it out and crush it; the NdFeB secondary waste is the solid waste generated after the NdFeB waste is processed by rare earth recovery;

[0038] S2, take 8g of the dried sample of step S1, and use a planetary ball mill for ball milling at room temperature and pressure (without atmosphere protection), with the grinding balls having a diameter of φ5 mm and a material of cemented carbide, the ball milling jar being made of stainless steel, the ball milling time being 2.5 h, the rotation speed being 400rpm, and the ball-to-material mass ratio being 10:1;

[0039] S3, the powder after ball milling in step S2 is passed through a 50-mesh sieve, and the powder that has not passed the sieve is repeated with ball milling in step S2 until it can pass through a 50-mesh sieve, and the sieved powder is placed in a sample bag and sealed for storage; the average particle size of the prepared micro-nano magnetic composite material is 50nm~5μm.

[0040] The performance of the NdFeB secondary waste and the prepared micro-nano magnetic composite material used in Example 1 was analyzed:

[0041] XRD patterns of NdFeB secondary waste and micro-nano magnetic composite materials Figure 1 As shown, analysis shows that the main components of NdFeB secondary waste are graphite, Fe3O4, and Fe2O3. After mechanical force chemical activation (ball milling), the diffraction peak intensity is significantly weakened, which indicates that the crystal structure of NdFeB secondary waste is destroyed under the action of mechanical force chemistry, and the material is transformed from a crystal structure to an amorphous state, and its amorphous degree is deepened. The existence of this amorphous phase can increase the strength of the interaction between the adsorbent material and the adsorbate, thereby improving the material's adsorption capacity for As(V).

[0042] SEM images of NdFeB secondary waste and micro-nano magnetic composite materials Figure 2 As shown, analysis shows that the raw materials ( Figure 2 (a) Before mechanochemical activation (ball milling), the particle size was large and the powder particles were severely agglomerated. After mechanochemical activation, the microscopic morphology of the material changed significantly, and the particle size of the material particles was significantly reduced under the mechanochemical action. In addition, the agglomeration between the material particles was effectively eliminated under the mechanochemical action, making the material particles more dispersed.

[0043] Mapping diagram of NdFeB secondary waste and micro-nano magnetic composite materials Figure 3 As shown, analysis shows that NdFeB secondary waste ( Figure 3 The Fe element agglomeration on the material surface of (a, b, c) is more serious, and the distribution of Fe element is more uniform after mechanochemical activation. This indicates that the exposure of iron oxide can be increased under the action of mechanochemical action, making iron oxide more evenly distributed on the material surface, which is beneficial to the complex reaction between the material and arsenate ions in the solution.

[0044] FT-IR images of NdFeB secondary waste and micro-nano magnetic composite materials are shown below: Figure 4 As shown in the figure, analysis shows that NdFeB secondary waste mainly has the following characteristic peaks: -1 The characteristic peak of Fe-O stretching vibration is located at 590 cm -1 The characteristic peak of the bending vibration of Fe-OH at 1090 cm -1 The characteristic peak of CO stretching vibration is located at 1635 cm -1 The characteristic peak of HOH water molecule bending vibration at 3420 cm -1The OH stretching vibration characteristic peak at . After mechanochemical activation, these functional groups and chemical bonds have undergone different degrees of changes. The peak intensities of the Fe-O stretching vibration characteristic peak, the Fe-OH bending vibration characteristic peak, and the CO stretching vibration characteristic peak have increased significantly and produced a small amount of offset. Among them, the increase in the peak intensity of the Fe-OH bending vibration characteristic peak after mechanochemical activation represents an increase in the Fe-OH content. Fe-OH will react with the arsenate ions in the solution to produce a complex to achieve the purpose of removing arsenic pollution. This is also one of the main reasons for the significant increase in the As(V) removal rate of the material after mechanochemical activation. Example 2

[0045] A method for preparing a micro-nano magnetic composite material from NdFeB secondary waste, comprising the following steps:

[0046] S1, placing the NdFeB secondary waste in an oven at 100°C, drying for 25 hours and then taking it out; the NdFeB secondary waste is solid waste generated after the NdFeB waste is processed by rare earth recovery;

[0047] S2, the dried sample of step S1 is ball milled with a planetary ball mill, the grinding balls are made of cemented carbide, the ball milling jar is made of stainless steel, the ball milling time is 2h, the rotation speed is 400rpm, and the ball-to-material mass ratio is 15:1;

[0048] S3, the powder after ball milling in step S2 is passed through a 50-mesh sieve, and the powder that has not passed the sieve is ball milled again in step S2 until it can pass through a 50-mesh sieve, and the sieved powder is placed in a sample bag and sealed for storage. Example 3

[0049] A method for preparing a micro-nano magnetic composite material from NdFeB secondary waste, comprising the following steps:

[0050] S1. Place the NdFeB secondary waste in an oven at 110°C and take it out after drying for 20 hours; the NdFeB secondary waste is solid waste generated after the NdFeB waste is processed by rare earth recovery;

[0051] S2, the dried sample of step S1 is ball-milled by a planetary ball mill, the grinding balls are φ5 mm in diameter, made of cemented carbide, the ball milling jar is made of agate, the ball milling time is 5 h, the rotation speed is 100 rpm, and the ball-to-material mass ratio is 8:1;

[0052] S3, the powder after ball milling in step S2 is passed through a 50-mesh sieve, and the powder that has not passed the sieve is ball milled again in step S2 until it can pass through a 50-mesh sieve, and the sieved powder is placed in a sample bag and sealed for storage. Example 4

[0053] An application of a micro-nano magnetic composite material in the treatment of arsenic-containing wastewater comprises the following steps:

[0054] S1. Take 0.05 g of the micro-nano magnetic composite material prepared in Example 1, add it to 50 mL of 10 mg / L arsenic-containing mine wastewater, and adjust the pH of the solution to 3. When adjusting the pH, 0.1 mol / L hydrochloric acid or 0.1 mol / L sodium hydroxide can be used as needed;

[0055] S2. The pH-adjusted solution was placed in a water bath constant temperature oscillator at a reaction temperature of 25°C and a rotation speed of 160 r / min for 120 min, and filtered through a 0.45 μm water filter membrane; the concentration of the filtrate was determined by ICP-OES.

[0056] The initial pH value of the solution can affect the entire reaction process by changing the existing form and chemical properties of pentavalent arsenic in the solution and the surface charge of the adsorption material. Figure 5 (a) shows the effect of micro-nano magnetic composite materials on As(V) removal rate and Zeta potential value under different initial pH values ​​of solution (1.0, 3.0, 5.0, 7.0, 9.0, 11.0). Analysis shows that the As(V) removal rate and Zeta potential value of micro-nano magnetic composite materials are significantly affected by the initial pH value of the solution. The effect of the initial pH value of the solution on the removal of As(V) by micro-nano magnetic composite materials shows a trend of first increasing and then decreasing. The Zeta potential value of the material decreases significantly with the increase of the initial pH value of the solution. When the initial pH value of the solution is 1.0, the As(V) removal rate of the micro-nano magnetic composite material is only 63.00%. As the initial pH value of the solution increases, the As(V) removal rate of the micro-nano magnetic composite material also increases, reaching a maximum of 94.33% at pH 3.0. Then, as the initial pH value of the solution increases, the As(V) removal rate of the micro-nano magnetic composite material gradually decreases, and decreases to 45.29% when the initial pH value of the solution is 11.0. Therefore, the analysis shows that when the initial pH value of the solution is 1.0, As(V) exists in the solution in the form of neutral H3AsO4 molecules, and the removal of As(V) by the micro-nano magnetic composite material is less affected by electrostatic effects. On the other hand, the micro-nano magnetic composite material partially dissolves under strong acid conditions, resulting in a reduction in the effective adsorption sites on the surface of the material, and thus the As(V) removal effect of the material is significantly reduced. As the initial pH value of the solution increases, the degree of deprotonation on the surface of the micro-nano magnetic composite material increases, resulting in an increase in the negative charge on the surface of the material, and the Zeta potential value of the material decreases, thereby weakening the electrostatic attraction between the negatively charged arsenate ions and the adsorption sites on the surface of the micro-nano magnetic composite material, and the As(V) removal rate of the material decreases. In addition, Figure 5 (a) It can be seen that the zero-point potential pH of the micro-nano magnetic composite material zpcWhen the pH value is greater than the zero potential pH, the negative charge and positive charge on the surface of the material are equal, and the net charge on the surface of the material is zero. zpc When the material surface is negatively charged, similarly, when the pH value of the solution is less than the zero potential pH zpc When the pH is greater than 9.1, the net charge on the surface of the material is negative, which repels the arsenate ions with the same negative charge. This is also the reason why the material removal rate drops significantly when the pH is 11.0. Therefore, pH 3.0 is determined to be the optimal initial pH value of the solution.

[0057] In addition, in actual mine wastewater containing As(V), it is inevitable that there are multiple coexisting ions that compete with arsenate ions for the adsorption sites of the adsorption material. Therefore, in order to simulate the real wastewater environment, the present invention selects the common cations (Cd 2+ , Ca 2 + Mg 2+ ) and anions (Cl - , sulfate) as coexisting ions, and three concentration gradients of 1, 10, and 100 mM were selected to carry out experimental research to study the effects of these coexisting ions on the removal of As(V) by micro-nano magnetic composites. Figure 5 (b) shows the effect of coexisting ions on the removal efficiency of As(V) by micro-nano magnetic composites. The order of influence of cations is: Ca 2+ > mg 2+ >Cd 2+ , the overall impact is small, among which Ca 2+ When the concentration was 100 mM, the As(V) removal rate of the micro-nano magnetic composite material was still 79.61%, with the least effect on Cd 2+ When the concentration was 100 mM, the As(V) removal rate of the material was 88.01%, indicating that the affinity of the micro-nano magnetic composite material to arsenate ions was much greater than that of the above three cations; - It has little effect on the removal of As(V) by micro-nano magnetic composites. - When the concentration was 100 mM, the As(V) removal rate of the micro-nano magnetic composite material was still 89.65%, only decreasing by 3.79%. This is because the negative monovalent Cl - The sulfate ions do not participate or participate in a small amount of competition with arsenate ions for effective adsorption sites on the surface of micro-nano magnetic composite materials. ) has the greatest impact on the material removal rate. When the concentration is 100 mM, the material has a removal rate of 63.76% for As(V). This is because the negative divalent The negatively charged ions form an electrostatic interaction with the negatively charged arsenate ions, and form a competitive adsorption relationship, which reduces the material's removal rate of As(V). The above experimental studies show that the micro-nano magnetic composite material still has a good removal effect on As(V) in the presence of coexisting ions in the solution. Therefore, in practical applications, the micro-nano magnetic composite material is suitable for treating complex arsenic-contaminated wastewater.

[0058] The removal mechanism of As(V) by the micro-nano magnetic composite material of the present invention is that the arsenate ions in the solution diffuse rapidly to the surface of the micro-nano magnetic composite material through electrostatic attraction, and then the arsenate ions react with the metal hydroxyl groups (Fe-OH) on the surface of the micro-nano magnetic composite material to form an inner sphere complex, which is fixed in the pores of the material. The removal mechanism diagram is shown in FIG. Figure 6 .

[0059] In order to evaluate the application potential of the micro-nano magnetic composite material, the present invention also examines its repeated regeneration performance. The hydroxide in the NaOH solution can coordinate and exchange with the arsenate ions on the surface of the material after As(V) adsorption, thereby achieving the purpose of regenerating the material. Therefore, this experiment uses 0.1 mol / L NaOH solution to desorb the micro-nano magnetic composite material after As(V) adsorption. Figure 7 As shown in the figure, after five adsorption-desorption cycles, the micro-nano magnetic composite material still maintains a good removal effect on As(V). With the increase of the number of cycles, the As(V) removal rate of the micro-nano magnetic composite material decreased from 94.33% to 73.56%, but it was still much greater than that of the raw material without mechanical chemical activation. Analysis shows that the reason for the decrease in the As(V) removal rate of the regenerated micro-nano magnetic composite material is the inevitable loss of the material during the adsorption-desorption cycle and the continuous occupation of the effective adsorption sites on the surface of the material by arsenate ions while the functional groups continue to weaken. In addition, the surface charge of the material changes, and the electrostatic effect on arsenate ions is weakened, resulting in a decrease in the As(V) removal ability of the micro-nano magnetic composite material after repeated regeneration. The excellent repeated regeneration performance of the micro-nano magnetic composite material reduces its use cost, making the micro-nano magnetic composite material have great application potential and economic benefits in the treatment of actual mine wastewater containing As(V). Example 5

[0060] The present invention also applies the micro-nano magnetic composite material to the treatment of chromium-containing wastewater, specifically:

[0061] ① The micro-nano magnetic composite material prepared in Example 1 was compared with ordinary Fe-C and other iron-based materials on the market; at room temperature of 25°C and pH = 7, 0.08 g of Fe-C, type A Fe-C, Fe-Si, ZVI, oxygen-containing acid radical Fe and the micro-nano magnetic composite material prepared in Example 1 were weighed respectively; 6 200 mL conical flasks were taken, 50 mL of chromium-containing wastewater was added to each of the materials in step S1, and then the conical flasks were placed in a water bath constant temperature oscillator, the speed was set to 200 r / min, the time was 90 min, the conical flask was taken out and filtered to obtain a filtrate, and the residual concentration of Cr(VI) was measured by a spectrophotometer, and the Cr(VI) removal rate was used as an indicator. The results are as follows: Figure 8 shown.

[0062] Analysis shows that the micro-nano magnetic composite material of the present invention has the best removal rate, which can reach 98.2%, followed by Fe-C; ZVI, A-type Fe-C, and oxygen-containing acid radical Fe have the lowest removal rate. The reason is that general iron-based materials need to undergo a reduction reaction with Cr(VI) at low pH to remove Cr(VI), so general iron-based materials cannot show good Cr(VI) removal performance in neutral solutions, while the micro-nano magnetic composite material prepared by ball milling method shows excellent adsorption, and can ensure good Cr(VI) removal ability without low pH.

[0063] ② Investigate the removal rate of Cr(VI) by different adsorbent materials: mainly compare the ability of Fe3O4, activated carbon, iron powder and the micro-nano magnetic composite material of the present invention to remove Cr(VI). At room temperature of 25°C and pH=7, weigh 0.08g of Fe3O4, activated carbon, iron powder and the micro-nano magnetic composite material prepared in Example 1 respectively; take 4 200 mL conical flasks, add 50 mL of chromium-containing wastewater respectively, and then add the above-mentioned different adsorbent materials respectively, put them into a water bath constant temperature oscillator, set the speed to 200 r / min, the time to 90 min, take out the conical flask and filter to obtain the filtrate, and measure the residual concentration of Cr(VI) with a spectrophotometer. Take the Cr(VI) removal rate as an indicator. The results are as follows: Fig. 9 shown.

[0064] The results show that the micro-nano magnetic composite material of the present invention has a good removal ability for hexavalent chromium solution, which is much better than iron powder, ferroferric oxide, and activated carbon in treating hexavalent chromium under the same conditions; and the micro-nano magnetic composite material has the best removal effect on Cr(VI) in a neutral environment, and does not need to adjust the pH, which is more conducive to on-site in-situ repair treatment. Iron powder, ferroferric oxide, etc. only show good removal effects under acidic conditions. By adjusting the pH of the hexavalent chromium solution and observing the removal rate of hexavalent chromium by iron powder and ferroferric oxide, it is found that they have a good removal effect under acidic conditions but almost no removal effect or very low removal effect under neutral conditions.

[0065] The present invention uses a mechanochemical method to activate NdFeB secondary waste, successfully prepares a micro-nano magnetic composite material and uses it for the treatment of As(V) / Cr(VI)-containing wastewater in mines, and studies the As(V) removal performance and mechanism of the micro-nano magnetic composite material. The raw material (NdFeB secondary waste) is mainly composed of Fe2O3, Fe3O4, and C. After mechanochemical activation, the material particles become more dispersed, the particle size decreases significantly, the specific surface area increases significantly, and the material diffraction peak intensity decreases significantly, indicating that it transforms from a crystal structure to an amorphous structure, and the amorphous degree increases. In addition, after mechanochemical activation, the peak intensity of the characteristic peak of Fe-OH bending vibration of the material is enhanced, indicating that its Fe-OH content increases. The experimental results of removing As(V)-containing wastewater show that the treatment result is best when the initial solution pH is 3. Combined with Zeta potential analysis, it is believed that the material is affected by electrostatic adsorption during the As(V) removal process. In addition, the material is less affected by coexisting ions, and still maintains a high removal rate for As(V) in the presence of high concentrations of coexisting ions, and has great application potential. The results of kinetic and isotherm fitting show that the adsorption process of As(V) by the material is more consistent with the quasi-second-order kinetic model and the Langmuir isotherm model, indicating that the removal of As(V) by the material is more inclined to chemical adsorption and monolayer adsorption, and the theoretical maximum adsorption capacity is 10.477 mg / g. Zeta, FT-IT, and XPS characterization test analysis confirm that the removal of As(V) by the material depends on the coordination exchange reaction between the material and As(V) to form an inner sphere complex. After five repeated regeneration tests, the material still maintains a high removal rate for As(V), proving that the micro-nano magnetic composite material generated by NdFeB secondary waste under high-energy ball milling is used to remove As(V) from water, which is low-cost, green and environmentally friendly, and has high economic benefits. The micro-nano magnetic composite material also has a good treatment effect on wastewater containing Cr(VI).

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing micro-nano magnetic composite materials from NdFeB secondary waste, characterized in that: The following steps are involved: S1. Place the NdFeB secondary waste in an oven at 100-110°C, dry for 20-25 hours, and then take it out; the NdFeB secondary waste is solid waste generated after the NdFeB waste is processed by rare earth recovery; by weight percentage, the NdFeB secondary waste includes 51.9% O, 24.7% C, and 23.4% Fe; S2, subjecting the dried sample of step S1 to mechanochemical treatment, wherein the mechanochemical treatment is ball milling, the ball milling time is 1-5h, the rotation speed is 100-500rpm, and the ball-to-material mass ratio is 5:1-20:1; the grinding ball material used in the ball milling is cemented carbide, and the ball mill jar material is any one of stainless steel, agate, and zirconium oxide; the NdFeB secondary waste is transformed from a crystalline structure to an amorphous state under the action of mechanochemical treatment; S3, the powder after ball milling in step S2 is passed through a 50-mesh sieve, and the powder that has not passed the sieve is ball milled again in step S2 until it can pass through a 50-mesh sieve, and the sieved powder is placed in a sample bag and sealed for storage.

2. The method for preparing micro-nano magnetic composite materials from NdFeB secondary waste according to claim 1, characterized in that: In the step S1, the NdFeB secondary waste is placed in an oven at 105° C. and dried for 24 hours.

3. The method for preparing micro-nano magnetic composite materials from NdFeB secondary waste according to claim 1 or 2, characterized in that: The ball milling time in step S2 is 2.5 h, the rotation speed is 400 rpm, and the ball-to-material mass ratio is 10:

1.

4. A micro-nano magnetic composite material prepared by the method according to any one of claims 1 to 3.

5. Use of the micro-nano magnetic composite material according to claim 4 in the treatment of arsenic-containing wastewater, characterized in that: The following steps are involved: S1. Take 0.03-0.08 g of the prepared micro-nano magnetic composite material, add it to 50 mL of arsenic-containing wastewater with a concentration of 10 mg / L, and adjust the pH of the solution to 2-5; S2. Place the pH-adjusted solution in a water bath constant temperature oscillator for oscillation reaction.

6. The use of a micro-nano magnetic composite material in the treatment of arsenic-containing wastewater according to claim 5, characterized in that: In the step S1, the pH of the solution is adjusted to 3.

7. The use of a micro-nano magnetic composite material in the treatment of arsenic-containing wastewater according to claim 5, characterized in that: In step S2, the reaction temperature of the water bath constant temperature oscillator is 25° C. and the rotation speed is 160 r / min.

8. Use of the micro-nano magnetic composite material according to claim 4 in the treatment of chromium-containing wastewater.

Citation Information

Patent Citations

  • Method for deep treatment of complex industrial wastewater by utilizing nano-zero-valent iron

    CN103253757A

  • Preparation method of porous carbon loaded zero-valent iron composite material

    CN113582284A

  • Method for recycling and reusing compression molding bonded magnet waste by using mechanical crushing method

    CN116900323A